Dieselov motor i okolica - Ormož, Krunoslav (Promet - Traffic&Transportation, 2012)
This paper provides a review of legal provisions effective in Europe and the states aimed at the reduction of harmful diesel exhaust emissions. Resolutions of the problems resulting from respective reduction of harmful emissions fall into three groups: improvements of the structure and technology of the engine, utilization of higher-quality fuels and lubricants and treatment of gases upon exhaust from the cylinder.